Venturing abroad in the Asia region : case study on projects in Indonesia and Malaysia - Chan, Choon Peng. (2009)
This dissertation is primarily a report based on findings from 2 (two) case studies of 2 (two) Singapore companies venturing into the Asean region, Company X, a major developer in Singapore venturing into property development in Malacca, Malaysia and Company B, a consultant in Singapore into consulting and contracting in the Riau Islands of Indonesia. Findings from the report cover the reasons for venturing abroad, their market niches, the utilisation of marketing expertise, the obstacles and risks involved and their views on venturing.